2016
DOI: 10.1016/j.cmi.2015.12.008
|View full text |Cite|
|
Sign up to set email alerts
|

Contamination of healthcare workers' mobile phones by epidemic viruses

Abstract: Mobile phones (MPs) are potential reservoirs of nosocomial bacteria, but few data are available concerning viruses. We aimed to evaluate the presence of virus RNA from epidemic viruses including metapneumovirus, respiratory syncytial virus, influenza viruses, rotavirus (RV) and norovirus on the MPs used by healthcare workers (HCWs) and to relate it to hygiene measures. An anonymous behavioural questionnaire about MP use at hospital was administered to the HCWs of four adult and paediatric departments of a univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 30 publications
2
41
0
3
Order By: Relevance
“…No obstante, esta variable no ha sido documentada en todos los estudios revisados, por lo que se propone para futuras revisiones abordar como eje central la multidrogorresitencia de las bacterias aisladas a partir de teléfonos celulares 48,49 . De igual forma, un elemento que vale la pena explorar en futuros estudios es la presencia de otros agentes tales como virus y hongos, entre otros, que pueden comportarse como patógenos nosocomiales de interés clínico presentes en los teléfonos celulares 10,50 .…”
Section: Duazaryunclassified
See 1 more Smart Citation
“…No obstante, esta variable no ha sido documentada en todos los estudios revisados, por lo que se propone para futuras revisiones abordar como eje central la multidrogorresitencia de las bacterias aisladas a partir de teléfonos celulares 48,49 . De igual forma, un elemento que vale la pena explorar en futuros estudios es la presencia de otros agentes tales como virus y hongos, entre otros, que pueden comportarse como patógenos nosocomiales de interés clínico presentes en los teléfonos celulares 10,50 .…”
Section: Duazaryunclassified
“…Se han reportado tasas de contaminación en teléfonos celulares de trabajadores de la salud que van desde el 47% hasta el 96% 6,7 , y entre el 9% y el 25% corresponden a microorganismos patógenos 8 . Esta conducta puede constituir un problema de salud pública considerando la posible contaminación cruzada mediante la transferencia de microorganismos pertenecientes a la flora normal de la piel, así como de potenciales agentes nosocomiales tales como bacterias, mohos y levaduras, entre otros [9][10][11] .…”
Section: Introductionunclassified
“…The entrance doors of the building have been equipped with infrared cameras to detect febrile persons and guide them to a specific zone of the consultation area to be cared for, allowing for a secure isolation in a dedicated part of the outpatient clinic for quick clinical investigation and diagnostics at the POC and eventually healthcare at the level 3 floor if contagious [23] ( Figure 5). As an example of prevention of fomite transmission, smartphones as well as stethoscopes are covered by a protective film [24].…”
Section: Infection Control and Security Circuitmentioning
confidence: 99%
“…Most of these findings were obtained for mobile devices used by patients, visitors, and health care workers in hospital settings. Bacteria reported include Acinetobacter spp., methicillin-sensitive and -resistant Staphylococcus aureus, vancomycin-resistant enterococci, Enterococcus, Streptococcus, Klebsiella, Proteus, Pseudomonas, Bacillus, and epidemic viruses (5,7,13,23,28). In a study comparing mobile phone use by health care providers, Lee et al (17) found significantly higher contamination by potentially pathogenic bacteria on smartphones (34.8%) than on other types of mobile phones (20.5%).…”
mentioning
confidence: 99%